Appraisal of cowpea cropping systems and farmers’ perceptions of production constraints and preferences in the dry savannah areas of Nigeria - Saba Baba Mohammed; Daniel Kwadjo Dzidzienyo; Muhammad Lawan Umar; Mohammad Faguji Ishiyaku; Pangirayi Bernard Tongoona; Vernon Gracen (CABI Agriculture and Bioscience)
Abstract Background Low plant density and wide intra-plant spacing in traditional cowpea cropping systems are among the factors responsible for low yield on farmers’ fields. Sole cropping and improved intercropping systems have been advocated in the last few years to increase yield in the dry savannah areas of Nigeria. This study investigated the level of adoption of high yielding cowpea cropping systems including factors that influenced their use and farmers’ perceived production constraints and preferences. A total of 420 farmers across 36 villages of northern Nigeria were interviewed, and data collected was analyzed using descriptive statistics to appraise farmers predominant cowpea cropping systems and factors that determine the use of sole versus intercropping were identified with the aid of binary logit regression. Furthermore, pairwise comparison ranking was deployed to understand farmers’ view of cowpea production constraints and preferred traits. Results The results revealed that, many of the farmers (42%) still grow cowpeas in the traditional intercropping and a good number (25%) cultivate the crop as a sole crop, while 23% had fields of cowpeas in both sole and intercropping systems. Farmers reported the incidence of high insect pests, limited access to land, desire to have multiple benefits, and assurance in the event of crop failure as reasons for preference for intercropping over sole planting. The pairwise comparison ranking of constraints and preferences revealed insect pests, Striga, drought and poor access to fertilizers as major constraints to increased productivity. Many farmers indicated high yield as the most preferred trait. Conclusions Findings indicate a need for increased education and training of cowpea farmers on the importance of growing cowpeas in sole cropping and or improved intercropping systems. Genetic improvement efforts should focus on developing cowpea varieties that address farmers production constraints and reflect the diversity of consumers’ preferences for the crop. Hence, breeding for resistance to insect pests and high yield is recommended as an important priority of cowpea breeding programmes in the region.